2018
DOI: 10.3390/agronomy8100233
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Genetic Diversity within A Middle-East Panel of Durum Wheat Landraces for Adaptation to Semi-arid Climate

Abstract: Drought is the major environmental factor limiting wheat production worldwide. Developing novel cultivars with greater drought tolerance is the most viable solution to ensure sustainable agricultural production and alleviating threats to food-security. Here we established a core-collection of landraces and modern durum wheat cultivars (WheatME, n = 36), from the Middle East region (Jordan, Palestine and Israel) aiming at unlocking the genetic and morpho-physiological adaptation to semi-arid environment conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…2). Such a magnitude of the contribution of each of the first three PCs rightly agreed with the results of research conducted in 2014 [65], which indicated the contribution of the PC1, PC2, and PC3 as 25.9%, 17.1%, and 13.3%, respectively and that in 2018 [42] which found PC1, PC2 and PC3 contributing 45.13%, 17.85%, and 14.71%, respectively in wheat germplasm studied. Similar results were also obtained by other researchers [66 -71].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2). Such a magnitude of the contribution of each of the first three PCs rightly agreed with the results of research conducted in 2014 [65], which indicated the contribution of the PC1, PC2, and PC3 as 25.9%, 17.1%, and 13.3%, respectively and that in 2018 [42] which found PC1, PC2 and PC3 contributing 45.13%, 17.85%, and 14.71%, respectively in wheat germplasm studied. Similar results were also obtained by other researchers [66 -71].…”
Section: Discussionsupporting
confidence: 89%
“…The results of multivariate cluster analyses revealed the existence of substantial variation among the durum wheat landrace accessions in the present study, which could be implied in the selection of appropriate accessions based on characters to be improved, as parents for producing transgressive segregants in a minimum period of time in the crop improvement program [42,74,75]. Accordingly, the accession PI 532306 of Al Dakhiliya can be chosen from the cluster-I as one of the parents for manipulating days to flowering with leaf sheath as identification marker; Similarly, PI 532291 and/ or PI 532 292 of Musandam can be chosen from cluster-II for improving grain weight with leaf color as marker-trait, PI 532239 of North Al-Batinah and/ or PI 532281 of Al Dakhiliya from cluster-III for improving spikelets/spike or grains/spike with coleoptile color as marker-trait, and PI 532303 or PI 532304 of Al-Dhofar governorate from cluster-IV for improving tiller number and grain length along with internode color as marker-trait.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Population structure and genetic diversity have been studied in several modern and landrace collections of durum wheat. Many studies have focused on panels from a restricted country/area such as landraces from Southern Italy ( Marzario et al, 2018 ), Iran ( Talebi and Fayaz, 2016 ), Spain ( Giraldo et al, 2016 ), Tunisia ( Robbana et al, 2019 ; Slim et al, 2019 ), Turkey and Syria ( Baloch et al, 2017 ), Palestine, Jordan and Israel ( Abu-Zaitoun et al, 2018 ), or specific breeding programs ( N’Diaye et al, 2018 ). Others have considered durum wheat collections of wider origin encompassing a few hundred entries.…”
Section: Introductionmentioning
confidence: 99%
“…All these negative influences threaten the sustainability of grain crop production. Decreased wheat productivity has caused devastating economic and sociological impacts [4]. In particular, the steady rise in population, loss of agricultural lands to sustainable urbanization, and decrease in resource availability owing to climate change pose serious threats to the safe production of wheat [3].…”
Section: Introductionmentioning
confidence: 99%